2015
DOI: 10.1007/s11356-015-5407-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of bisphenol A and some heavy metal ions by polydivinylbenzene magnetic latex particles

Abstract: In this study, magnetic polydivinylbenzene latex particles MPDVB with a core-shell structure were tested for the removal of bisphenol A (BPA), copper Cu(II), lead Pb(II), and zinc Zn(II) from aqueous solutions by a batch-adsorption technique. The effect of different parameters, such as initial concentration of pollutant, contact time, adsorbent dose, and initial pH solution on the adsorption of the different adsorbates considered was investigated. The adsorption of BPA, Cu(II), Pb(II), and Zn(II) was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Graphene-oxide-based nanocomposites contained hydrophobic (i.e., graphene basal planes with aromatic rings and various hydrophilic groups such as hydroxyl (–OH) and carboxyl (O=C–O) [69]. BPA also had both hydrophobic (i.e., phenyl groups) and hydrophilic (i.e., hydroxylic) functional groups [70]. Due to the comparable configuration of BPA and GO-polymer composites, it was expected that two types of adsorbent-adsorbate interactions might be responsible for the adsorption of BPA onto the composites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Graphene-oxide-based nanocomposites contained hydrophobic (i.e., graphene basal planes with aromatic rings and various hydrophilic groups such as hydroxyl (–OH) and carboxyl (O=C–O) [69]. BPA also had both hydrophobic (i.e., phenyl groups) and hydrophilic (i.e., hydroxylic) functional groups [70]. Due to the comparable configuration of BPA and GO-polymer composites, it was expected that two types of adsorbent-adsorbate interactions might be responsible for the adsorption of BPA onto the composites.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the comparable configuration of BPA and GO-polymer composites, it was expected that two types of adsorbent-adsorbate interactions might be responsible for the adsorption of BPA onto the composites. One probable interaction is hydrogen bonding (H-bond) between oxygen-containing groups of the materials and/or with the benzene rings on the materials surface that can also act like hydrogen bond donors and hydroxylic functional groups of BPA [70,71]. The other one may be π–π interactions between the benzene rings contained in BPA and GO-based materials.…”
Section: Resultsmentioning
confidence: 99%
“…Yantasee et al [19] utilized thiol functionalized superparamagnetic nanoparticles to remove heavy metals from aqueous systems. Polydivinylbenzene magnetic latex particles were prepared for the removal of BPA and some heavy metal ions [20]. Moreover, Zhang et al [21] found that magnetite nanoparticles (Fe 3 O 4 MNPs) exhibited ultrahigh adsorption towards chlorotetracycline, and many other studies suggested that the magnetic composite adsorbent could remove pollutants [22,23,24].…”
Section: Introductionmentioning
confidence: 99%